2011
DOI: 10.1161/strokeaha.110.606509
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline in Vascular Cognitive Impairment and Vascular Dementia After Stroke

Abstract: Abstract-Cognitive decline after stroke is more common than stroke recurrence. Stroke doubles the risk of dementia and is a major contributor to vascular cognitive impairment and vascular dementia. Neuropathological studies in most cases of dementia in the elderly reveal a large load of vascular ischemic brain lesions mixed with a lesser contribution of neurodegenerative lesions of Alzheimer disease. Nonetheless, few pharmacological studies have addressed vascular cognitive impairment and vascular dementia aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 44 publications
(34 reference statements)
2
43
0
17
Order By: Relevance
“…This improvement of survival also fits in with a decrease in MP production when HBEC are treated with CTC in vitro. These data support a role for CTC in reducing MP production by stabilizing the microvascular endothelium, similar to what is seen in other vascular pathologies (32)(33)(34)(35). CTC therapy can be proposed for clinical studies of human patients to improve recovery from CM, as it is already used as a food supplement for malnourished children and has low toxicity.…”
supporting
confidence: 79%
“…This improvement of survival also fits in with a decrease in MP production when HBEC are treated with CTC in vitro. These data support a role for CTC in reducing MP production by stabilizing the microvascular endothelium, similar to what is seen in other vascular pathologies (32)(33)(34)(35). CTC therapy can be proposed for clinical studies of human patients to improve recovery from CM, as it is already used as a food supplement for malnourished children and has low toxicity.…”
supporting
confidence: 79%
“…8 A number of studies have also shown that citicoline appears to be a drug able to provide "safe" neuroprotection by enhancing protective endogenous pathways. 13,21 These properties suggest that citicoline can be recommended for use in patients with vascular cognitive impairment, vascular dementia, or Alzheimer's disease with significant cerebrovascular disease. It seems to have a beneficial impact on several cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is one of the most common causes of cognitive impairment (2)(3)(4). According to different subtypes and diagnostic criteria of stroke, 17-92% of patients present with cognitive impairment 3 months after a stroke (5).…”
Section: Introductionmentioning
confidence: 99%